Softskill Training , Outbound Training And Knowledge Sharing On The Performance Of Perumdam Tirta Hita Buleleng Employees - Yudi Prastiwi, Ni Luh Putu Eka; Didiet Prayogo, Nyoman; Ni Made, Sri Ayuni; Widnyani, Ni Made (Universitas Ibn Khladun Bogor, 2023)
This test has results to see whether soft skill training , outbound training, along with knowledge sharing have an impact on the performance of Tirta Hita Buleleng employees. This test was carried out at the Tirta Hita Buleleng Regional Drinking Water Company. The population used in this test is all employees who work at Perumdam Tirta Hita Buleleng, namely 75 employees. The rating scale uses a Likert scale which then the data obtained is processed using multiple linear regression analysis techniques. in this test the findings obtained were 1) the more consistent the soft skill training was , the more employee performance at Perumdam Tirta Hita Buleleng 2) the more consistent outbound training was carried out regularly, resulting in increased employee performance at Perumdam Tirta Hita Buleleng. 3) The more knowledge sharing is carried out , so that the performance of employees at Perumdam Tirta Hita Buleleng increases.